Levels of homeotic protein function can determine developmental identity: evidence from low-level expression of the Drosophila homeotic gene proboscipedia under Hsp70 control. - Cribbs, D L (1995)
The autonomous selector capacity of the homeotic proboscipedia (pb) gnee of the Drosophila Antennapedia Complex was tested. We introduced into the germline a P element containing a transcriptional fusion of a mini-gene for pb (normally required for formation of the labial and maxillary palps of the mouthparts) and the Hsp70 promoter. Uninduced expression of this Hsp70:pb element (HSPB) directs a novel, fully penetrant dominant transformation of antennae toward maxillary palps. Gene dosage experiments varying the number of HSPB elements indicate that the extent of the dominant transformation depends on the level of PB protein. At the same time, expression from the transgene also rescues recessive pb mutations. Finally, HSPB function may override the dominant antennal transformations caused by Antennapedia (Antp) mutations in a dose-sensitive manner, directing a switch of the antennal disc-derived appendage from ectopic leg to ectopic maxillary palp. This switch correlated with strikingly reduced ANTP protein accumulation when PB concentrations exceeded a genetically defined threshold level. These observations support a crucial role for quantitative aspects of pb function in determining segmental identity, including cross-regulatory events involved in this determination.